Bioremediation of microplastic using microbes isolated from mangrove sediments / Helen Shnada Auta - Helen Shnada , Auta (2018)
The presence of microplastics and their continuous accumulation in the marine environment, poses a threat to the entire ecosystem. In this study, 22 bacteria were isolated from plastic/microplastic-inundated mangrove soil and were screened for the potential to degrade polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET) and polystyrene (PS) using the clear zone method. Nine isolates grew and demonstrated significant clear zones on synthetic media containing the different microplastics as carbon source. Shake flask experiments were carried out to further evaluate the biodegradability potential of the isolates individually and in consortia. Similarly, biodegradation experiments were carried out to evaluate the effect of different inoculum concentrations of the microbes on microplastic biodegradation. Degradation was monitored by recording the weight loss of the different microplastics and evaluating the growth response of the isolates to different times of exposition in Bushnell-Haas broth. The degradation extent was validated by assessment of the morphological, structural and surface changes through SEM and FTIR analyses. The results revealed that 6.2% of PE microplastics was reduced by Bacillus gottheilii. Maximum degradation of PP microplastics (6.4%) was attained by Rhodococcus ruber, while the maximum weight loss of PS (7.4%) and PET (6.6%) was recorded on treatment with Bacillus cereus. Engineering the microbes into consortia of different treatments (A, B, C, and D) formed from the combination of the microbes showed that maximum weight loss of PE (1.4%) and PET (1.2%) was attained on treatment with Treatment D (which consisted of all gram-positive bacteria) while maximum weight loss of PP (8.8%) and PS (21.4%) was attained by Treatment A (consisting of all nine bacteria). On treatment with different concentrations of the microbes, highest weight loss of PET microplastics by Treatment D (7.2%) was achieved on treatment with 40% v/v inoculum concentration while highest weight loss for PS microplastics by Treatment A (30.8%) was attained on treatment with 10% v/v inoculum concentration. Bioremediation of soil contaminated with PET and PS microplastics and bioaugmented with 10% v/v of Treatment A was studied for a period of 90 days under field conditions in mangrove soil using the soil burial technique. At the end of 90 days, significant reduction in weight of both microplastics was observed in the microbially amended and the unamended soil portions. Maximum weight loss (17.8%) was observed in PET microplastics subjected to microbial treatment (microbially amended portion) while maximum weight loss of 19% was observed in PS microplastics buried in the unamended soil, suggesting that mangrove soil harbours a diversity of microbes with potential to degrade microplastics. SEM and FTIR analyses showed major structural, morphological, and surface changes and the formation of bacterial biofilm on the microplastic surfaces after degradation. The study thus, confirmed the ability of the marine microbes to utilize PE, PP, PET, and PS microplastics as carbon source and indicate positive potential towards remediation of microplastic-contaminated environments.